Production Budget for Bell Peppers in Palm Beach County, Florida - John VanSickle; Scott Smith; Eugene McAvoy (EDIS)
FE809, a 4-page fact sheet by John VanSickle, Scott Smith, and Eugene McAvoy, provides an overview of bell pepper production practices for Palm Beach County producers, including a per-acre composite budget breaking down the specific cost components. Includes references. Published by the UF Department of Food and Resource Economics, December 2009.